Molecular characterisation of Czech Clostridium difficile isolates collected in 2013-2015 - Krutova, M; Nyc, O; Matejkova, J; Allerberger, F; Wilcox, M H; Kuijper, E J (International journal of medical microbiology, 2016)
Clostridium difficile is a leading nosocomial pathogen and molecular typing is a crucial part of monitoring its occurrence and spread. Over a three-year period (2013-2015), clinical C. difficile isolates from 32 Czech hospitals were collected for molecular characterisation. Of 2201 C. difficile isolates, 177 (8%) were non-toxigenic, 2024 (92%) were toxigenic (tcdA and tcdB) and of these, 677 (33.5%) carried genes for binary toxin production (cdtA, cdtB). Capillary-electrophoresis (CE) ribotyping of the 2201 isolates yielded 166 different CE-ribotyping profiles, of which 53 were represented by at least two isolates for each profile. Of these, 29 CE-ribotyping patterns were common to the Leeds-Leiden C. difficile reference strain library and the WEBRIBO database (83.7% isolates), and 24 patterns were recognized only by the WEBRIBO database (11.2% isolates). Isolates belonging to these 53 CE-ribotyping profiles comprised 94.9% of all isolates. The ten most frequent CE-ribotyping profiles were 176 (n=588, 26.7%), 001 (n=456, 20.7%), 014 (n=176, 8%), 012 (n=127, 5.8%), 017 (n=85, 3.9%), 020 (n=68, 3.1%), 596 (n=55, 2.5%), 002-like (n=45, 2.1%), 010 (n=35, 1.6%) and 078 (n=34, 1.6%). Multi-locus sequence typing (MLST) of seven housekeeping genes performed in one isolate of each of 53 different CE-ribotyping profiles revealed 40 different sequence types (STs). We conclude that molecular characterisation of Czech C. difficile isolates revealed a high diversity of CE-ribotyping profiles; the prevailing RTs were 001 (20.7%) and 176 (027-like, 26.7%).
Keywords: Genetic Variation; Adolescent; MLST; senioři; Clostridioides difficile; Infant, Newborn; Clostridium difficile; Male; Female; mladý dospělý; dítě; klostridiové infekce; novorozenec; Aged; multilokusová sekvenční typizace; Middle Aged; Young Adult; Molecular Epidemiology; Česká republika; ribotypizace; Bacterial Toxins; Capillary electrophoresis ribotyping; předškolní dítě; genetická variace; mužské pohlaví; Toxin genes; Genotype; ženské pohlaví; Adult; kojenec; Hospitals; Czech Republic; Molecular typing; bakteriální toxiny; nemocnice; Child; senioři nad 80 let; mladiství; dospělí; Clostridium Infections; lidé středního věku; genotyp; Multilocus Sequence Typing; Ribotyping; tcdC; Aged, 80 and over; lidé; Humans; molekulární epidemiologie; Child, Preschool; Infant